2020
DOI: 10.1111/jjns.12329
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and assessment of induration by ultrasonography after chemotherapy administration through a peripheral intravenous catheter

Abstract: AimsFollowing chemotherapy, induration may occur. This study was conducted to survey induration incidence and risk factors, and investigation for actual condition of induration.MethodsA cohort study was conducted for survey of incidence and risk factors, and a cross‐sectional observation study was conducted to examine actual condition of induration. The sites of chemotherapy administration were recorded, and these were observed on the next treatment day. Clinical nurses judged the presence or absence of indura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
1
12
0
3
Order By: Relevance
“…Reports about peripheral intravenous catheterization‐induced induration are few; however, the condition of the subcutaneous tissue (thrombus, subcutaneous edema, and vessel wall thickening) in this case was the same as in a previous report. In that report, the induration sites were observed using ultrasonography, wherein the observation was only conducted on the next treatment day in patients who were receiving chemotherapy via peripheral intravenous catheters 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports about peripheral intravenous catheterization‐induced induration are few; however, the condition of the subcutaneous tissue (thrombus, subcutaneous edema, and vessel wall thickening) in this case was the same as in a previous report. In that report, the induration sites were observed using ultrasonography, wherein the observation was only conducted on the next treatment day in patients who were receiving chemotherapy via peripheral intravenous catheters 3 …”
Section: Discussionmentioning
confidence: 99%
“…injection site. 2,3 A previous study reported the incidence of induration after chemotherapy as 17.4%. If induration is found by physicians or nurses, inserting catheter to the affected site is avoided.…”
mentioning
confidence: 99%
“…Vein stiffness (which is very similar to induration) was only noted by the expert nurses in this study. Palpation is the only assessment method for induration in a clinical setting (Abe-Doi et al, 2020). Expert nurses are more likely to observe vein stiffness because, compared to newly graduated nurses, the former tend to use tactile input to a greater extent than visual information (Forsberg & Engström, 2018).…”
Section: Focusing On the Patient's Unique Characteristics And Choosmentioning
confidence: 99%
“…According to Marsh, Webster, Larsen, Cooke, et al (2018a), phlebitis was the most common cause of a PVC failure (17%), followed by occlusion/infiltration (14%) and dislodgement (10%); moreover, those complications were statistically more significant among female patients. Female patients are also more likely to experience an infiltration or extravasation (Abe‐Doi, Murayama, Komiyama, & Sanada, 2020; Hwang, Shin, Choi, & Park, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This same study also reported that subcutaneous edema in the catheterization site can occur immediately after chemotherapy with some specific drugs (Murayama et al, 2019). In a cross‐sectional observational study of 69 participants using ultrasonography, the incidence of abnormal findings (e.g., subcutaneous edema, thickened vessel walls, thrombi) on the next treatment day following chemotherapy administration, without catheter failure, was 8.7% (Abe‐Doi et al, 2020a). This finding suggests that tissue damage may remain at the catheterization site over time, even when chemotherapy administration was completed without clear signs of extravasation.…”
Section: Introductionmentioning
confidence: 99%